Interface thermal behavior in nanomaterials by thermal grating relaxation. (March 2019) - Palla, Pier Luca; Zampa, Sonia; Martin, Evelyne; Cleri, Fabrizio
Highlights: The heat equation solution for systems with interface resistances is discussed. A new molecular dynamics approach to interface resistance evaluation is developed. Size effects in thermal transfer are explained via a non-local heat equation. A experimental thermal grating approach to interface resistance measurement is proposed. Abstract: We study the relaxation of a thermal grating in multilayer materials with interface thermal resistances. The analytical development allows for the numerical determination of this thermal property through the Approach to Equilibrium Molecular Dynamics and suggests an experimental setup for its measurement. Possible non-diffusive effects at the nanoscale are take into consideration by a non-local formulation of the heat equation. As a case study, we numerically apply the present approach to silicon grain boundary thermal resistance.